Privacy and confidentiality in telemedicine: a literature review - Imelda Ritunga; Cempaka Harsa; Jemima Santoso; Mellyanawati; Stefani Nurhadi; Elizabeth Nugraheni; Shabila Ikha Pertiwi; Nazwa Syahlimar Alkatiri (Christian Journal for Global Health)
Telemedicine has become an essential service, especially since the pandemic, transforming traditional face-to-face, doctor-patient consultations into virtual interactions. This shift presents several ethical challenges, particularly concerning patient privacy and confidentiality. Ensuring the quality and ethical standards of telemedicine services requires addressing these concerns. This literature review synthesizes key issues and recommendations related to privacy and confidentiality in telemedicine based on 14 selected articles. The inclusion criteria were English, full-text availability, and publications from the last ten years. Articles that were not original research or irrelevant to the review were excluded. Privacy challenges include the lack of an integrated system and the absence of national standards, raising concerns about unauthorized access to sensitive information. Confidentiality challenges center around patients' concerns regarding the security of their electronic health records, especially with the use of third-party services. Protecting patient privacy and confidentiality during telemedicine consultations is a critical, ethical issue, and healthcare providers must ensure that these concerns are adequately addressed to maintain patient trust and comfort.